Pengaruh Knowledge Sharing dan Gaya Kepemimpinan Demokratis Terhadap Kepuasan Kerja Karyawan Bali Buda Restoran Ubud - Swandewi, Ni Kadek Ayu; Sari, Putu Ratna Juwita (Jurnal Ilmiah Global Education, 2024)
Employee job satisfaction plays a central role in the success of a company. When employees are satisfied with their jobs, they tend to be more productive, enthusiastic, and committed to the company's goals. This study aims to analyze the influence of knowledge sharing and democratic leadership styles on the job satisfaction of employees at Bali Buda Restaurant in Ubud. The number of respondents involved in this study was 49 individuals. We collected data using a questionnaire and employed multiple linear regression analysis as the analysis technique. We conducted hypothesis testing using t-tests and F-tests. The research results indicate that knowledge sharing has a positive and significant influence on job satisfaction. Democratic leadership style also has a positive and significant impact on job satisfaction. Collectively, knowledge sharing and democratic leadership styles significantly influence job satisfaction.